The role of gut microbiota in gout: Is gut microbiota a potential target for gout treatment - Tong, Shuting; Zhang, Peiyu; Cheng, Qi; Chen, Mo; Chen, Xin; Wang, Zitao; Lu, Xiaoyong; Wu, Huaxiang (Frontiers in Cellular and Infection Microbiology, 2022)
Numerous studies have demonstrated that gut microbiota is essential for the host’s health because it regulates the host’s metabolism, endocrine, and immune systems. In recent years, increasing evidence has shown that gut microbiota plays a role in the onset and progression of gout. Changes in the composition and metabolism of the gut microbiota, result in abnormalities of uric acid degradation, increasing uric acid generation, releasing pro-inflammatory mediators, and intestinal barrier damage in developing gout. As a result, gout therapy that targets gut microbiota has drawn significant interest. This review summarized how the gut microbiota contributes to the pathophysiology of gout and how gout affects the gut microbiota. Additionally, this study explained how gut microbiota might serve as a unique index for the diagnosis of gout and how conventional gout treatment medicines interact with it. Finally, prospective therapeutic approaches focusing on gut microbiota for the prevention and treatment of gout were highlighted, which may represent a future avenue in gout treatment.